Endoscopic Ultrasound Through-the-Needle Biopsy for the Diagnosis of an Abdominal Bronchogenic Cyst - Jessica Cassiani; Stefano Francesco Crinò; Erminia Manfrin; Matteo Rivelli; Armando Gabbrielli; Alfredo Guglielmi; Corrado Pedrazzani (Korean Society of Gastrointestinal Endoscopy, 2021)
A 57-year-old woman with epigastric pain was diagnosed with a 6-cm abdominal cystic lesion of unclear origin on cross-sectional imaging. Endoscopic ultrasound (EUS) demonstrated a unilocular cyst located between the pancreas, gastric wall, and left adrenal gland, with a regular wall filled with dense fluid with multiple hyperechoic floating spots. A 19-G needle was used to puncture the cyst, but no fluid could be aspirated. Therefore, EUS-guided through-the-needle biopsy (EUS-TTNB) was performed. Histological analysis of the retrieved fragments revealed a fibrous wall lined by "respiratory-type" epithelium with ciliated columnar cells, consistent with the diagnosis of a bronchogenic cyst. Laparoscopic excision was performed, and the diagnosis was confirmed based on the findings of the surgical specimen. Abdominal bronchogenic cysts are extremely uncommon, and a definitive diagnosis is commonly obtained after the examination of surgical specimens due to the lack of pathognomonic findings on cross-sectional imaging and poor cellularity on EUS-guided fine-needle aspiration cytology. EUS-TTNB is useful for establishing a preoperative histological diagnosis, thus supporting the decision-making process.